Agency and intentionality-dependent experiences of moral emotions. (1st October 2020) - Bland, A.R.; Schei, T.; Roiser, J.P.; Mehta, M.A.; Zahn, R.; Seara-Cardoso, A.; Viding, E.; Sahakian, B.J.; Robbins, T.W.; Elliott, R.
Abstract: Moral emotions are thought to influence moral behaviour by providing a driving force to do good and to avoid doing bad. In this study we examined moral emotions; specifically, guilt, shame, annoyance and feeling "bad" from two different perspectives in a moral scenario; the agent and the victim whilst manipulating the intentionality of the harm; intentional and unintentional. Two hundred participants completed a moral emotions task, which utilised cartoons to depict everyday moral scenarios. As expected, we found that self-blaming emotions such as shame and guilt were much more frequent when taking on the perspective of the agent whilst annoyance was more frequent from the victim perspective. Feeling bad, however, was not agency-specific. Notably, when the harm was intentional, we observed significantly greater shame ratings from the perspective of the agent compared to when the harm was unintentional. In addition, we also found clear gender differences and further observed correlations between moral emotions and personality variables such as psychoticism and neuroticism.